Growing up in Ireland: Constructions of Gender and Childhood 1800-1860 - HATFIELD, MARY (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2018)
This thesis examines cultural constructions of childhood and the experiences of children in Ireland from 1800 to 1860. At the beginning of the nineteenth century childhood was a fluid concept with a variety of meanings and responsibilities dependent on class, gender, and religious identity. By 1860 the idea of what childhood was supposed to be had been consolidated to a large degree by the middle classes, who rejected the lavish opulence of the aristocracy and the economic dependency of the working classes to create their own brand of child-rearing. The project explores ways in which adults dealt with children, particularly within the family and in educational institutions across the island of Ireland. This holistic approach towards the middle-class child?s social world utilises medical and educational literature, religious tracts, personal correspondence, school archives, and material culture sources. It facilitates an understanding of gender roles, children?s participation in middle-class domesticity, and the use of education by middle-class families to shape a cultural narrative of childhood. This project considers normative discourses of ?ideal? Irish childhood, critically assessing the diversity of childhood experiences and ways in which child and society confronted each other.
APPROVED
Keywords: Childhood; gender; class identity; nineteenth-century; Ireland; education; history of education; middle-classes; masculinity; secondary schools; children's clothing; history; gender studies; Children's studies; cultural history